Ionic composition of late Pleistocene ice wedges (IW-5 and IW-7) of the Batagay yedoma, Verkhoyansk District of Yakutia - Yurij K Vasil extquotesinglechuk (PANGAEA, 2025)
This work delineates the macroelements compositions in the Late Pleistocene syngenetic ice wedges (IW-5 and IW-7) situated in the bottom section of the Batagay Yedoma complex. Ice samples were extracted from ice wedges at 10 cm intervals using Makita and Bosch GSR drills equipped with steel ice crowns of 51 mm in diameter. The composition of macroelements in the ice wedges was analyzed using the ion chromatograph Steyer. The concentrations of potassium, sodium, calcium, magnesium, chlorine, nitrates, and sulfates were measured. The mineralization of Late Pleistocene ice wedges ranges from 67 to 425 mg/l. In the analyzed ice wedges, calcium predominates among the cations (IW-5 ranging from 17.8 to 82.5 mg/l, IW-7 from 12.0 to 52.1 mg/l). Magnesium ranks second (IW-5 ranging from 3.1 to 13.6 mg/L, IW-7 ranging from 2.6 to 8.3 mg/l). Sodium and potassium cations are present in minimal concentrations: Na - IW-5 ranges from 0.8 to 6.8 mg/L, IW-7 from 0.45 to 4.0 mg/l, and K – IW-5 from 17.8 to 82.5 mg/L, IW-7 from 1.1 to 5.6 mg/l. Nitrates dominate among the anions. The nitrate concentration varies from 6.9 to 27.9 mg/L for IW-5 and from 5.0 to 54.8 mg/l for IW-7. Mean nitrate concentration IW-5: 14.5 mg/l; IW-7: 12.2 mg/l. In IW-5, the concentration of sulfate anions ranges from 2 to 17 mg/l, with an average of 6.4 mg/L, whereas the chloride concentration ranges from 1 to 7 mg/l, averaging 2.6 mg/l. The sulfate concentration in IW-7 ranges from 1.4 to 40.5 mg/L, with an average of 6.4 mg/L; the chloride concentration ranges from 1.13 to 4.5 mg/l, with an average of 2 mg/l. In IW-5, the chloride-to-sulfate ratio ranges from 0.16 to 1.45, with an average of 0.44; in IW-7, the ratio ranges from 0.04 to 1.12, with an average of 0.47. Upon comparing these data with the chloride to sulfate ratios in ground ice and surface water in North-West Siberia, we observe that the ratios most closely resemble those found in the snowfields of the Seyakha (Mutnaya) River valley on the northern Yamal Peninsula, where the chloride to sulfate ratio is 0.54, in rainwater on the Yamal Peninsula with a ratio of 1.44, and in segregated ice on the first terrace of Bely Island, where the ratio is 1.08. The chloride to sulfate ratio in IW-5 and IW-7 significantly differs from that of cryopegs (ratio 49.45) and the majority of the massive ice in the Yamal Peninsula (68.91; 26.39; 9.77, etc.). The ionic composition of the ice wedges indicative that they was formed from thawed snow generated under the influence of continental air masses. The ice wedges, named IW-5 and IW-7, were sampled with cordless drills from BOSCH GSR 18V-EC TE and Makita DDF481RTE 188 equipped with special titan drilling nozzles. Ice for isotope analysis was sampled along the vertical axes of exposed IWs with steps through each 0.2-0.3 m. For samples from ice, a method was used to measure the mass concentration of Ca2+, Mg2+, Na+, K+, NH4+ cations in samples of drinking, mineral, natural and waste water by ion chromatography FR.1.31.2005.01738. For the determination of anions, the method of measuring the mass concentration of Cl-, SO4-, NO3- in samples of drinking, mineral, natural and wastewater by ion chromatography FR.1.31.2005.01724 was used. The method of measuring the mass concentration of ions in samples of natural, drinking and wastewater by ion chromatography HDPE F 14.1:2:4. 132-98.Measuring instruments: ion chromatographic system "Stayer", detection limit for chloride ion 0.02 mg/l.